Portrait of Picasso as a young man an interpretive biography - Mailer, Norman 1923-2007 (Atlantic Monthly Press, 1995)
An interpretive biography of Picasso's life and work as a young man, discussing the influence of his first great love, Fernande Olivier.
Keywords: Olivier, Fernande <1881-1966> - Et les hommes; Picasso, Pablo <1881-1973>; Picasso, Pablo <1881-1973> - Amis et relations; Olivier, Fernande -- Relations with men; Picasso, Pablo <1881-1973> -- Friends and associates; Picasso, Pablo -- 1881-1973; Geschichte 1881-1915; Schilderijen; Malerei; Artist couples -- France -- Paris; Artists -- France -- Biography; Frankreich; Biografie